Assessing the impact of the COVID-19 pandemic on the mental health of female entertainment workers in Cambodia: a group model building approach - Chua, Calida S.; Ansah, John P.; Tep, Sovanvorleak; Oy, Sreymom; Ung, Mengieng; Yi, Siyan (Frontiers in Public Health, 2024)
BackgroundThe COVID-19 pandemic has intensified global mental health challenges, particularly for vulnerable groups like female entertainment workers (FEWs), a critical HIV-affected population in Cambodia. Already facing pre-existing inequalities, FEWs encountered heightened difficulties due to the pandemic’s disruption of their livelihoods. Their susceptibility to mental health problems is exacerbated by poverty and the occupational stressors they regularly endure. This study aims to identify COVID-19-related factors adversely impacting the mental well-being of FEWs in Cambodia and explore potential interventions to mitigate these effects.MethodsIn December 2021, we conducted a two-day workshop in Phnom Penh using a group model-building approach with stakeholders from diverse backgrounds to gather collective insights. We employed the qualitative system dynamics method of causal loop diagram mapping to visualize the factors affecting FEWs’ mental health. Based on participants’ perceptions and experiences, we constructed a causal loop diagram to develop a comprehensive systems perspective.ResultsThe workshop involved 27 stakeholders, including representatives from national institutions (n = 3), local NGOs (n = 17), an international NGO (n = 1), and the FEW community (n = 6). Our analysis identified 13 feedback loops highlighting key factors influencing the mental well-being of FEWs during the pandemic. These factors included the loss of family members, financial instability, fear of COVID-19 infection, the pressure of children’s homeschooling due to school closures, and food insecurity. In response, stakeholders proposed a range of interventions, including alternative vocational training, increased awareness of mental health issues, access to mental health services, and programs targeting gender-based violence within FEW communities.ConclusionA collaborative, multi-sectoral approach is crucial to addressing the mental health challenges of FEWs in Cambodia. Prioritizing the establishment of accessible, affordable, and high-quality mental health services, alongside the implementation of targeted interventions, is essential to mitigate the negative mental health impacts of the pandemic and enhance the overall well-being of FEWs.